2020
DOI: 10.1101/2020.04.29.066415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The SecA motor generates mechanical force during protein translocation

Abstract: The Sec translocon moves proteins across lipid bilayers in all cells. The Sec channel enables passage of unfolded proteins through the bacterial plasma membrane, driven by the cytosolic ATPase SecA. Whether SecA generates mechanical force to overcome barriers to translocation posed by structured substrate proteins is unknown. Monitoring translocation of a folded substrate protein with tunable stability at high time resolution allowed us to kinetically dissect Secdependent translocation. We find that substrate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…A rational interpretation is that the ribosome bound TF, working as mechanical foldase, generate a mechanical power to pull the protein from confined ribosomal tunnel while the free cytosolic state only behaves as holdase, slows down the refolding rate for efficient folding. Similarly, we have shown an oxidoreductase enzyme DsbA, associated with periplasmic mouth of SecYEG tunnel, speeds up the folding of translocating polypeptide which experiences a force of 7-11 pN in the SecYEG pore 5,45 . This acceleration in protein folding generates an excess mechanical work which reduces one third of the energy consumption for translocation along with increasing the translocation velocity.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…A rational interpretation is that the ribosome bound TF, working as mechanical foldase, generate a mechanical power to pull the protein from confined ribosomal tunnel while the free cytosolic state only behaves as holdase, slows down the refolding rate for efficient folding. Similarly, we have shown an oxidoreductase enzyme DsbA, associated with periplasmic mouth of SecYEG tunnel, speeds up the folding of translocating polypeptide which experiences a force of 7-11 pN in the SecYEG pore 5,45 . This acceleration in protein folding generates an excess mechanical work which reduces one third of the energy consumption for translocation along with increasing the translocation velocity.…”
Section: Discussionmentioning
confidence: 75%
“…9C). This makes sense as otherwise, if the protein gets folded by itself, its translocation through the SecYEG pore might get hampered due to the geometric constraints or excess energy might be needed by SecA or other unfoldases to disrupt the tertiary folded structure 5,33,48 . However, DnaJ and DnaK along with the GrpE makes the substrate folded by simply restoring its innate ability to refold under force, which has been clearly observed at equilibrium force condition (Fig 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of SecYEG by SecA initiates the step-wise translocation of secretory proteins across the membrane. The reconstituted SecYEG-SecA complex was shown to generate a mechanical force of about 10pN ( Robson et al, 2007 ; Gupta et al, 2020 ). Consequentially, several models were proposed on how the high conformational flexibility of SecA might be used for the ATP-dependent and stepwise translocation of a preprotein across the SecYEG channel ( Erlandson et al, 2008a , b ; Kusters et al, 2011 ; Gouridis et al, 2013 ; Ernst et al, 2018 ; Fessl et al, 2018 ; Corey et al, 2019 ; Komarudin and Driessen, 2019 ).…”
Section: The Secyeg Complex In the Resting And Active Statementioning
confidence: 99%
“…SecA ATPase, one of the essential components of the Sec machinery provides a major pathway to aid translocation of cytosol proteins across or into the cytoplasmic membrane. [3][4][5][6][7][8][9] SecA is considered as an attractive target by researchers in order to nd novel antibacterial drugs because it is a conserved and essential protein in all bacteria and absent in humans. [10,11] Several studies carried out have shown that inhibition of SecA can lead to bacteriostatic and bactericidal effects [12] .…”
Section: Introductionmentioning
confidence: 99%